Estudio preliminar de tres modelos de destiladores solares para producir sal y agua potable (ING) - Nandwani, Shyam S.; Marín Vonkoller, Silvia (Uniciencia, 1986)
We have constructed three solar stills of areas 0.5-1.0 m2 to produce salt and potable water, using local technology and local materials. We have studied the thermal efficiency of these stills as a function of solar intensity, covers, geometrical configuration, quantity of water, salt concentration and artificial cooling of the cover. Some of the important results are: still with glass cover destill more water than still with plastic cover, thermal efficiency vary between 10-30%, amount of water which can be evaporated and condense is 2-4 l/day/m2, exist 25-60% of loss of water in the still and finally artificial cooling of the cover can be accelerate the process of condensation, etc. Finally we have mentioned the chemical analysis of destilled and normal tap water.